WormBase: a modern Model Organism Information Resource. Issue Volume 48:Issue D1(2020) (23rd October 2019) - Harris, Todd W; Arnaboldi, Valerio; Cain, Scott; Chan, Juancarlos; Chen, Wen J; Cho, Jaehyoung; Davis, Paul; Gao, Sibyl; Grove, Christian A; Kishore, Ranjana; Lee, Raymond Y N; Muller, Hans-Michael; et al.
Abstract: WormBase (https://wormbase.org/ ) is a mature Model Organism Information Resource supporting researchers using the nematode Caenorhabditis elegans as a model system for studies across a broad range of basic biological processes. Toward this mission, WormBase efforts are arranged in three primary facets: curation, user interface and architecture. In this update, we describe progress in each of these three areas. In particular, we discuss the status of literature curation and recently added data, detail new features of the web interface and options for users wishing to conduct data mining workflows, and discuss our efforts to build a robust and scalable architecture by leveraging commercial cloud offerings. We conclude with a description of WormBase's role as a founding member of the nascent Alliance of Genome Resources.